The Effectiveness of Mindfulnes Based Stress Reduction (MBSR) Increasing Resilience in Review of the Economic Social Status of ODGJ Companion Families at the Oepoi Health Center, Kupang - Kinanggi, Ratnasari; Suroso; Pratitis, Niken (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to analyze the effectiveness of Mindfulness Based Stress Rreduction (MBSR) in increasing resilience and test the difference in resilience levels reviewed from the socioeconomic status of ODGJ companion families at the Oepoi Health Center, Kupang City. Resilience is the ability of individuals to manage themselves both within individuals such as individual emotions and thoughts as well as from outside individuals in overcoming problems, difficulties and unpleasant experiences in a good way. MBSR helps individuals manage stress and reduce impulsive reactions to emotions, as well as focus attention on the present moment, which reduces anxiety about the future. Socioeconomic status is the classification of people in social classes based on the same level of economic status.the number of samples in this study is 54 subjects, the sampling technique uses purposive sampling so that the subjects who received MBSR intervention were 19 people with The data analysis method uses the Mann Whitney U Test and the Kruskal Wallis test.